“Belago” Simulasi Strategi Perang dan Ekonomi Dalam Media Permainan Papan - Robertus Adi Oktavian; Samuel Gandang Gunanto (Institut Seni Indonesia Yogyakarta, 2018)
In this era, people certainly tend to play digital games, whether on computers, consoles or other gadgets. But no doubt that board games or board games remain the choice of games that entertain a number of circles. Board games that still exist today played by people such as Chess, Monopoly, Uno, Ludo, Snake Ladder, and others are examples of the many board games that can still be enjoyed.According to Boardgame community data on the www.boardgame.id website, the number of board game enthusiasts in 2017-208 is increasing because more and more indie developers are starting to create board games with creative ideas, which attract the attention of board game enthusiasts to try and play with his friends. With this in mind, the design and creation of a board game called